Trends and concepts in post‐mastectomy breast reconstruction. Issue 8 (14th February 2016) - Farhangkhoee, Hana; Matros, Evan; Disa, Joseph
Abstract : A number of factors have contributed to a paradigm shift in US post‐mastectomy breast reconstruction. The increasing numbers of contralateral prophylactic mastectomies strongly correlated to a rise in implant‐based reconstructions. Autologous reconstruction, however, has faced a number of barriers including technically complicated perforator flaps and declining reimbursements. As such, a market concentration has developed within high volume microsurgical centers. As more patients receive radiation, the timing and method of reconstruction has become a controversial topic. J. Surg. Oncol. 2016;113:891–894 . © 2016 Wiley Periodicals, Inc.